The design of a mini hydro generator / Nik Hosni Iskandar Nik Azlan - Nik Azlan, Nik Hosni Iskandar (2010)
Renewable energy is a common issue that has been discussed continuously since the past few decades. Attaining and developing new ideas to create and restore energy to be used and at the same time not affecting the environment are one of the biggest hurdles that the issue tries continuously to overcome. Along the way, there are many inventions and ideas that have been stumbled upon to generate these renewable energies. The basic design of the project is in fact a system whereby energy is produced by the principles of generating electricity by using kinetic energy. In this design, the system is initiated by fluid flow of the water in the pipeline thus causing a movement of rotation of the water turbine. As the turbine rotates, this will turn the shaft that is attached to an electrical generator. This will result in the change of the kinetic energy of the turbine be turned into the electrical energy produced by the rotation of the shaft inside the electrical generator. The energy produced will be stored in a battery for mobility and convenience of usage. As an aspect of design, the current result has exceeded initial aim based on wattage and voltage capacity. With potential as big as this, the project promises a future in its functionality and application in the near future.